Governance Strategies in Underwater Inspection State-Owned Enterprises: A Study on the Implementation of Public-Private Partnerships (PPP) - Ardhian Budi Sulistiyo; Rachma Fitriati (PT Mattawang Mediatama Solution, 2023)
This article aims to analyze the need to conduct underwater inspection at a State-Owned Enterprise (SOE) using the application of the Public Private Partnership (PPP) concept. However, until now, the SOE still uses the services of a third party to fulfill this need. The use of third-party services impacts the high allocation of the SOE's operational budget for underwater inspection costs. This study uses qualitative research methods with data collection techniques through in-depth interviews, literature studies, and field observations from January to August 2023. This study's results show that applying the four dimensions of PPP - identify key stakeholders, identify stakeholder needs, address stakeholder needs, and evaluate performance - is appropriate for the governance of underwater inspection implementation. The recommendation for the next governance strategy is to implement acquisition as a follow-up to the PPP concept.